Introduction From Populism to Decolonisation: How We Remember in the Twenty-First Century. Issue 1 (4th August 2020) - Forsdick, Charles; Mark, James; Spišiaková, Eva
This article introduces, and contextualises, the contributions to the collection The global crisis in memory . Since the 1980s, the idea of 'coming to terms with the past', shaped by the values of neoliberal economics and liberal politics, became part of a globally-powerful consensus over how societies should overcome violent and traumatic experiences. In the 2010s, in the context of the global rise of populist nationalisms, political hostility linked to global migration, and increasingly vocal criticisms of a neoliberal order, this consensus was powerfully challenged. Rather than rejecting memory politics, new political formations have in fact embraced them. The white resentment embodied in the 'History Wars' controversy in Australia; legislation such as the Polish 'Holocaust Bill'; the growing scepticism of African states towards the International Criminal Court; or the rewriting of the histories of Indian independence by Hindu nationalists all reveal the ways in which diverse movements critiqued and reworked previous memory tropes. At the same time, attempts to decolonise western memory have engaged actively with previous manifestations of memory around which apparent consensus had been constructed. Moreover, these various new memory practices increasingly have their own alternative internationalisms too, reaching across or beyond regions in new transnational formations.